Narrative change in emotion-focused psychotherapy: a study on the evolution of reflection and protest innovative moments - Mendes, Inês (2011)
Innovative moments (IMs) are exceptions to a client’s problematic self-narrative in the therapeutic dialogue. The innovative moments coding system is a tool which tracks five different types of IMs*action, reflection, protest, reconceptualization and performing change. An in-depth qualitative analysis of six therapeutic cases of emotion-focused therapy (EFT) investigated the role of two of the most common IMs*reflection and protest*in both good and poor outcome cases. Through this analysis two subtypes (I and II) of reflection and protest IMs were identified, revealing different evolution patterns. Subtype II of both reflection and protest IMs is significantly higher in the good outcome group, while subtype I of both IMs types does not present statistically significant differences between groups. The evolution from subtype I to subtype II across the therapeutic process seems to reflect a relevant developmental progression in the change process.